2008
DOI: 10.1146/annurev.anthro.37.081407.085120
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Kinship, Marriage, and Reproduction

Abstract: This review examines the implications of new kinship practices for anthropological theory, with a special focus on recent research in gay and lesbian kinship and assisted reproduction. The article begins with an account of the theoretical contexts in which kinship studies have been conducted and a brief survey of some of the older literature on alternative systems of marriage and family formation in preindustrial and modern societies. The emphasis then turns to current discussions of how gay men and lesbian wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…But the notion of "fraud" is complicated in defining family relationships. Given the importance accorded the extended family in U.S. immigration laws of the post-1965 period, relying on DNA technology to prove the existence of familial relationships is problematic given that kinship bonds may be forged beyond heteronormative nuclear family units (Carsten 2004;Franklin and McKinnon 2001;Heinemann and Lemke 2013;Howell 2009;Levine 2008;Schneider 1980). Interviews revealed that lawyers were aware some people knowingly claimed biologically unrelated people as blood relatives in reunification petitions.…”
Section: Dna Testing For Family Reunificationmentioning
confidence: 99%
“…But the notion of "fraud" is complicated in defining family relationships. Given the importance accorded the extended family in U.S. immigration laws of the post-1965 period, relying on DNA technology to prove the existence of familial relationships is problematic given that kinship bonds may be forged beyond heteronormative nuclear family units (Carsten 2004;Franklin and McKinnon 2001;Heinemann and Lemke 2013;Howell 2009;Levine 2008;Schneider 1980). Interviews revealed that lawyers were aware some people knowingly claimed biologically unrelated people as blood relatives in reunification petitions.…”
Section: Dna Testing For Family Reunificationmentioning
confidence: 99%
“…Less evidently, they thereby increase the scope of their perceptions and network connections (Davidoff & Hall, 1987: 202, 227;Hamabata, 1990: 28;Lomnitz &Pérez-Lizaur, 1987: 118;Robertson, 1991: 41). A similar logic applies to non-discrimination on the basis of sexual orientation (Levine, 2008). Research about gay and lesbian entrepreneurship is still seminal, but undoubtedly some enterprising family firms have found use for this tactic (Schindehutte, Morris, & Allen, 2005;Willsdon, 2005).…”
Section: Equal Opportunities Irrespective Of Sex Rolesmentioning
confidence: 99%
“…Where it is available it is adapted to its particular cultural context. For example, it is used very differently in the socially conservative culture of Lebanon (Clarke, 2008) than in the socially liberal cultures of urban China and India (Gates, 1993;Khanna, Sudha, & Rajan, 2009; see generally Levine, 2008). We can expect that it will become an increasingly utilized strategy of heirship.…”
Section: New Reproductive Technologiesmentioning
confidence: 99%
“…In recent years, legislation, news outlets, and even television programs have dedicated their attention to the ''crisis of the family.'' This is not surprising considering that the past several decades have witnessed scientific advances in reproductive technologies and sociopolitical movements that have challenged the ''typical'' Western family structure (see Blackwood 2005;Butler 2002;Edwards et al 1999;Franklin 2001;Hayden 1995;Levine 2003Levine , 2008Ragoné 1996;Strathern 1992c;Thompson 2001;Weston 1991).…”
Section: Introductionmentioning
confidence: 99%